The economic effects of pre-school education and quality - Sarah Cattan; Claire Crawford; Lorraine Dearden (Institute for Fiscal Studies (IFS), 2014)
The Effective Pre-School, Primary and Secondary Education (EPPSE) project is the first large-scale British study on the effects of different pre-school experiences on children's outcomes. It enables researchers to look at the impact of both pre-school education and pre-school quality not only on short-term education outcomes, but also on long-term education and possible future labour market outcomes for a cohort of individuals who did not have access to universal pre-school education. It is these long-term economic consequences that are the focus of this report.
Keywords: 330